John Locke and the ethics of belief - Wolterstorff, Nicholas (Cambridge ; New York : Cambridge University Press, 1996)
In this important study Nicholas Wolterstorff interprets and discusses the ethics of belief which Locke developed in the latter part of Book IV of his Essay Concerning Human Understanding. After lengthy discussions on the origin of ideas, the nature of language, and the nature of knowledge, Locke got around to arguing what he indicated in the opening Epistle to the Reader to be his overarching aim: how we ought to govern our belief, especially (though by no means only) on matters of religion and morality. Professor Wolterstorff shows that what above all placed this topic on Locke's agenda was the collapse, in his day, of a once-unified moral and religious tradition in Europe into warring factions. Locke's epistemology was thus a culturally and socially engaged one; it was his response to the cultural crisis of his day.
Convinced also that of genuine knowledge we human beings have very little, Locke argued that instead of following tradition we ought to turn "to the things themselves" and let "Reason be your guide." This view of Locke, in which centrality is given to the last book of the Essay, invites an interpretation of the origins of modern philosophy different from most of the current ones. Accordingly, after discussing Hume's powerful attack on Locke's recommended practice, Wolterstorff argues for Locke's originality and discusses his contribution to the "modernity" of post-sixteenth-century philosophy.
1. Rationality in everyday life. I. The Vision: Let Reason Be Your Guide in Believing. II. Applications of the Vision. III. Implementation of the Vision -- 2. Hume's attack: why implementing Locke's practice is not always doing one's best -- 3. Locke's originality. I. How Descartes's Project Differed. II. Where Locke Was Original -- 4. Locke and the making of modern philosophy.
Includes bibliographical references and index.
Keywords: Locke, John, -- 1632-1704.; Locke, John, -- 1632-1704 -- Religion